2012
DOI: 10.2169/internalmedicine.51.7906
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Solitary Fibrous Tumor of the Pleura with Malignant Transformation and Non-islet Cell Tumor-induced Hypoglycemia due to Paraneoplastic Overexpression and Secretion of High-molecular-weight Insulin-like Growth Factor II

Abstract: A 41-year-old man was diagnosed with a solitary fibrous tumor (SFT) of the pleura in the posterior mediastinum. Despite two surgeries for excision, the SFT recurred and progressed with direct invasion of the chest wall and bone metastases. He was hospitalized because of cerebral infarction and presented with recurrent severe hypoglycemia fourteen years later. High-molecular-weight (HMW) insulin-like growth factor II (IGF-II) was identified in the serum and tumor using Western blotting and immunohistochemistry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…We reviewed case reports of NICTH associated with paraneoplastic production of IGF-2 from 2008 to 2012 (Table 3) [17-38]. On our review of literature, we identified 22 published reports of NICTH with elevated IGF-2 levels causing hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed case reports of NICTH associated with paraneoplastic production of IGF-2 from 2008 to 2012 (Table 3) [17-38]. On our review of literature, we identified 22 published reports of NICTH with elevated IGF-2 levels causing hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Low IGF-I levels in patients with NICTH are attributed to chronic attenuation of GH secretion, due to the negative feedback of IGF-II ( 9 ). Several studies have shown that NICTH due to HMW-IGF-II can be diagnosed using western blot analysis ( 10 12 ). Hata et al ( 10 ) examined HMW-IGF-II by using preoperative and postoperative blots and demonstrated that HMW-IGF-II disappeared postoperatively, which is considered to be a useful therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…Different criteria have been developed to assign malignant or benign classification to SFTs based on histologic features, age, location, size, sessile/pedunculated nature [ 5 , 18 ]. Nevertheless, SFTs classified as benign have been observed to undergo malignant transformation and recur at local and distant sites [ 8 , 9 , 12 , 17 , 27 ]. In view of this unpredictable behavior and the increased risk of retroperitoneal SFTs to recur than other SFTs, it is judicious to follow-up all cases of retroperitoneal SFTs irrespective of satisfying the criteria for benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal SFTs are a distinct sub-group of extra-pleural SFTs, often incidentally discovered during imaging for an unrelated pathology and present with non-specific symptoms, mainly abdominal pain, hip pain and urinary symptoms [ 6 ]. Extra-thoracic SFTs have been classically described as benign tumors but recent studies with larger numbers of cases and longer follow up have demonstrated the existence of a subgroup of tumors that exhibit a malignant clinical course with local and distant recurrence even after surgical excision [ 4 , 7 , 8 ]. Adverse outcomes are usually associated with atypical histological features (nuclear pleomorphism, increased cellularity, necrosis or mitoses greater than 4/10 HPF) and size greater than 10 cm [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%